2019
DOI: 10.1177/0265407519841719
|View full text |Cite
|
Sign up to set email alerts
|

Affection substitution: The effect of pornography consumption on close relationships

Abstract: Scholars have stated that humans have a fundamental need to belong, but less is known about whether individuals can use other resources to substitute for close relationships. In this study, 357 adults reported their level of affection deprivation, their weekly pornography consumption, their goals for using pornography (including life satisfaction and loneliness reduction), and indicators of their individual and relational wellness. We hypothesized that individuals might consume pornography as a coping mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 76 publications
0
13
0
1
Order By: Relevance
“…As wellbeing is generally considered to be positively associated with the frequency of sexual intercourse [ 35 ], a decrease in the frequency of sexual intercourse may indicate a decrease in mental wellbeing, even when autoerotism and pornography are used as substitutes for sexual intercourse. It was hypothesised that pornography consumption is used as a coping mechanism to deal with affection deprivation [ 36 ]. However, its long-term effect on mental health is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…As wellbeing is generally considered to be positively associated with the frequency of sexual intercourse [ 35 ], a decrease in the frequency of sexual intercourse may indicate a decrease in mental wellbeing, even when autoerotism and pornography are used as substitutes for sexual intercourse. It was hypothesised that pornography consumption is used as a coping mechanism to deal with affection deprivation [ 36 ]. However, its long-term effect on mental health is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a relationship break-up may be a more powerful trigger to use SEIM to compensate for the lack of sexual interactions with a former partner. The study of Hesse and Floyd ( 2019 ) showed some evidence that SEIM use can be used to deal with the perception of affection deprivation in close relationships. However, when it comes to adolescents’ SEIM uses, no research has explored how profound contextual changes other than the COVID-19 pandemic can potentially stimulate SEIM use.…”
Section: Discussionmentioning
confidence: 99%
“…None of the guidelines mentioned viewing of internet pornography. While repeated viewing of internet pornography can be problematic (Wetterneck et al, 2012), occasional viewing can help reduce the negative emotionality of loneliness for individuals who live alone (Hesse & Floyd, 2019;Sharkey et al, 2020;Stark et al, 2017). Future research is warranted on the sexual experiences and expectations of adults during the pandemic.…”
Section: Implications and Conclusionmentioning
confidence: 99%